(untitled) (International Journal of Physiotherapy, 2025)
Background: Pelvic girdle pain refers to pain in the pelvis during pregnancy. It can significantly impact a woman’s quality of life by limiting her mobility. It can cause significant physical disability and can have a psychological impact on the individual. However, it has no identified risk factors or determinants associated with it. This study aimed to understand the extent of this problem and identify potential determinants in primigravida postpartum females. Methods: Primigravida females with a mean age of 24.5±3.33 within 2 to 6 months of the postpartum period were interviewed via a questionnaire enquiring about the presence of pelvic pain, body mass index (BMI), and type of delivery. Further, the piriformis muscle tightness assessment and pregnancy mobility index quantification were performed. Outcomes assessed were the presence of pelvic pain and the Score of Pregnancy Mobility Index in those positive for pelvic pain. Possible associations of pelvic pain with type of delivery, BMI, and piriformis tightness were studied using a non-parametric test. Results: The study found that 62% of the women experienced pelvic pain, with the most significant limitations in household chores and outdoor activities. Tightness in the piriformis muscle was identified as a potential risk factor for pelvic pain. (p<0.05). Conclusion: These findings suggest that pelvic pain is a common issue after childbirth and can significantly impact a woman’s ability to perform daily tasks. Piriformis tightness is a potential determinant of pelvic pain in primigravida postpartum females; thus, targeting its tightness may be a potential strategy for preventing or managing pelvic pain in primigravida postpartum females.